Peer support for the primiparous mother with postpartum depression: a scoping review - Eka Septianingrum; Cesa Septiana Pratiwi; Fitria Siswi Utami (International Journal of Health Science and Technology, 2021)
Postpartum depression is a global problem throughout the world. Research studies have found that based on this background, the researchers would know peer support for primiparous mothers with postpartum depression. This scooping review method used the framework from Arksey and O'Malley focusing on the PICO framework. Result: it showed that peer support for primiparous mothers with postpartum depression was very limited. Conclusion: This support is expected to be able to realize the biological and psychological well-being of mothers in the face of postpartum depression and to adapt their changing roles and minimize the occurrence of postpartum depression.